Proposed M-Payment System Using Near-Field Communication and Based on WSN-Enabled Location-Based Services for M-Commerce - Sun-Kuk Noh; Seong-Ro Lee; DongYou Choi (International Journal of Distributed Sensor Networks)
Advances in mobile communication and information technology have resulted in wireless sensor network (WSN) systems in which mobile phones (smart phones) can be used to conduct a wide variety of commercial, social, entertainment, and file-sharing transactions. In particular, mobile commerce (m-commerce) allows users to conduct payment, business, and service transactions over portable mobile devices. This trend has been enhanced by the development of near-field communication (NFC) technology and the increased market for NFC-embedded (smart phones). NFC technology is a standards-based wireless communication technology that allows data to be exchanged between devices located a few centimeters apart, such as radio-frequency identification (RFID tags and readers). To refine the m-commerce process in the NFC-based mobile environment, we study NFC and location-based services propose a WSN-hosted m-payment system based on these technologies.